Fostering self, resiliency, and transformational leadership among middle leaders in basic education through the Lasallian Enrichment and Accompaniment Program (LEAP) - DeLeon, Abram Michael (Animo Repository, 2023)
The role of middle leaders in schools is central to school effectiveness, yet many assume middle leadership without any relevant training on crucial aspects of the job. This study examined the challenges and support opportunities for fourteen (14) middle leaders in a junior high school in Bacolod City, Negros Occidental, Philippines. The needs assessment results obtained through survey questionnaires and informal interviews with senior administrators revealed that middle leaders in the school moved into their roles without proper transition and a formal professional development (PD) program for decades. Further, the survey results suggest that there needs to be more training and preparation for this priority group regarding their managerial and leadership skills. This prompted the researcher to implement a PD program entitled “Lasallian Enrichment and Accompaniment Program (LEAP)”. Through quantitative and open-ended questionnaires, post-session meetings, and leadership activity sheets, middle leaders perceived LEAP as successful in reflecting on their leadership philosophy and practices and improving their leadership skills and competency in a collaborative environment. Further, the researcher found that considering the broader school context and aligning the participants’ needs and challenges with the training design is critical to the success of the PD program. The participants perceived the process of reflection and collaboration as an effective underlying mechanism of change. This action research illuminates what constitutes an effective middle leaders’ PD program that aims to increase job preparation and perceived job performance. It is recommended to conduct a further study to capture the PD program’s effectiveness and establish evidence that it improved middle leaders’ leadership practices.